2021
DOI: 10.3233/ves-201582
|View full text |Cite
|
Sign up to set email alerts
|

Association between vestibular function and rotational spatial orientation perception in older adults

Abstract: BACKGROUND: Spatial orientation is a complex process involving vestibular sensory input and possibly cognitive ability. Previous research demonstrated that rotational spatial orientation was worse for individuals with profound bilateral vestibular dysfunction. OBJECTIVE: Determine whether rotational and linear vestibular function were independently associated with large amplitude rotational spatial orientation perception in healthy aging. METHODS: Tests of rotational spatial orientation accuracy and vestibular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 68 publications
4
13
0
Order By: Relevance
“…In agreement with previous reports using the same or a similar orientation task ( Israël et al, 1995 ; Marlinsky, 1999 ; Jáuregui-Renaud et al, 2008 ; Anson et al, 2021 ), in this study, over-estimation of rotation was more frequent than underestimation. The orientation test design included rotations of increasing amplitude/duration, this allowed overestimation of duration to be easily interpreted as increased amplitude, which could give rise to overestimation errors.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In agreement with previous reports using the same or a similar orientation task ( Israël et al, 1995 ; Marlinsky, 1999 ; Jáuregui-Renaud et al, 2008 ; Anson et al, 2021 ), in this study, over-estimation of rotation was more frequent than underestimation. The orientation test design included rotations of increasing amplitude/duration, this allowed overestimation of duration to be easily interpreted as increased amplitude, which could give rise to overestimation errors.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with previous reports (Jáuregui-Renaud et al, 2008;Anson et al, 2021), the analysis of this study showed no independent influence of sex on updating orientation after passive rotations in the horizontal plane. This finding was consistent with the observed lack of influence of physical activity on the performance of the orientation test, given that men reported more physical activity than women.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations